Trust and Crisis Management in the European Union An Institutionalist Account of Success and Failure in Program Countries - Győrffy, Dóra (Springer International Publishing, 2018)
This book addresses and explains the divergent economic and political outcomes of the financial crisis in the eight European Union member states which needed a bailout program: Cyprus, Greece, Hungary, Ireland, Latvia, Portugal, Romania and Spain. Looking at crisis management as a series of relationships where cooperation is essential, this book focuses on the essential role of trust during the process. It argues that the presence or absence of trust during the negotiation and implementation of the bailout program leads to self-reinforcing cycles of success and failure. The analysis of these eight countries also explores the institutional sources of trust - it shows that a commitment to limited government is associated with both economic success and resistance to populism. The final chapter considers the implications for the future of the EU and calls attention to the importance of strengthening domestic institutions in order to bridge the gap between concerns over moral hazard and expectations of solidarity.